Asian dust from land to sea: processes, history and effect from modern observation to geological records. (May 2020) - Wan, Shiming; Sun, Youbin; Nagashima, Kana
Abstract: Production, transport and deposition of aeolian dust from land to sea closely interact with regional environment and global climate. This Special Issue addresses transport of aeolian dust from the Asian inland to the Loess Plateau and North Pacific Ocean and their possible links to oceanic ecosystem, global climate and even human activity, over various timescales. The papers in this volume are multidisciplinary in nature and include sedimentology, mineralogy, geochemistry, environmental magnetism and climate modelling on multi-timescales from interannual, glacial–interglacial to tectonic timescales. Based on modern observation, geological records and modelling, this Special Issue offers new insights especially into aeolian provenance, dynamics controls on dust production, a novel marine aeolian proxy, as well as long-term aeolian input to the marginal basins of NE Asia and its influence on oceanic productivity. This issue provides a good example for future comprehensive studies of source-to-sink processes of Asian dust from land to sea.